Conceptual understanding of acids and bases concepts and motivation to learn chemistry. Issue 1 (2nd January 2017) - Cetin-Dindar, Ayla; Geban, Omer
ABSTRACT: The purpose of this study was to investigate the effect of 5E learning cycle model oriented instruction (LCMI) on 11th-grade students' conceptual understanding of acids and bases concepts and student motivation to learn chemistry. The study, which lasted for 7 weeks, involved two groups: An experimental group (LCMI) and a control group (the traditional teacher-centered instruction [TTCI]). Based on multivariate analysis of covariance results, the LCMI students outperformed the TTCI students in terms of conceptual understanding about acids and bases. Similarly, the students from the experimental group scored higher motivation and this difference was found to be statistically significant. These findings demonstrated that instruction based on learning cycle model provide students a deeper conceptual understanding, foster high-order thinking, engage them in the learning process, and influence their motivation to learn by increasing the relevance of school chemistry to their daily lives.